New Technologies in the 21st century ESL/ EFL classroom - A Web Quest - assisted reading lesson - Papadaki, Aggeliki; Karagianni, Eleni; Driga, Anna Maria (Eximia, 2023)
The purpose of the particular article is to design an original reading lesson integrating the use of literary texts available online. In the first part, there is a brief description of the teaching situation. In the second part, there is a literature review, while in the third part, the original reading lesson is presented. More specifically, there is a presentation of the aims and objectives set in the lesson, the teaching materials and finally, the teaching process with detailed analysis of every stage (pre/while/post-reading). Finally, there is a discussion and a conclusion summarizing the ideas presented in the previous stages.